Performance Evaluation of Feedback-based Bandwidth Allocation Algorithms for 802.11e MAC - G. Boggia; P. Camarda; L. Grieco; S. Mascolo; A. Stefanelli (2007 IEEE 65th Vehicular Technology Conference - VTC2007-Spring, 2007)
In order to provide service differentiation in 802.11 wireless local area networks, the 802.11e working group has recently proposed the hybrid coordination function (HCF) along with a HCF controlled channel access (HCCA). However, the 802.11e proposal does not specify an effective bandwidth allocation algorithm. Recently, to overcome this limitation, a control theoretic framework has been proposed in literature. Within such a framework, this paper proposes a new allocation algorithm based on a proportional-integral-derivative (PID) controller. Moreover, a performance comparison among the simple Scheduler introduced by 802.11e standard and three bandwidth allocations algorithms, designed using different dynamic regulators, has been carried out. Ns-2 simulation results showed that the best trade-off between packet delays and number of admitted flows is achieved by a properly tuned PID regulator.
Keywords: Channel allocation; Regulators; Wireless LAN; Proposals; Three-term control; Pi control; Proportional control; Dynamic scheduling; Scheduling algorithm; Algorithm design and analysis